Situation Awareness Analysis of Clinic Organizers Towards Risk and Benefits Perception of Compliance in Clinic Operating Permit - Bisukma Kurniawati (Poltekkes Kemenkes Surabaya, 2016)
The main purpose of this research is to compose recommendation so that clinic organizers submissive towards clinic operating permit. The background of this research is the low rate of compliance of clinic towards operating permit prolongation based on the punctuality of prolongation permit and the high rate of clinic that still running without operating permit. The population of this reasearch are 58 clinics that have operating permit issued in year 2006-2008. Sample is taken by simple random sampling. The sample is calculated using slovin method and the result are 51 clinics. This research used primary data from clinic organizers that renew the permit prolongation on time, late, and clinics that did not prolong their permit but still running the clinic, and secondary data from Dinas Kesehatan Kota Surabaya. Based on time and data collection, the methods of this research is cross sectional study because the research variable measurement only done at one specific time using observation technique and questionnaire as data collection tool. Then the analysis is done to determine the connection between variables, and the result is used to provide recommendation in order to set policies for Pemerintah Kota Surabaya. The result of this research can be concluded that how high the rate of situation awareness from clinic organizers, proportion of benefit perception and risk perception of clinic organizers towards permit. Keywords: situation awareness, risk perception, benefit perception, compliance